2017
DOI: 10.3892/ol.2017.5822
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformation and thyroid metastasis from underlying renal cell carcinoma, an unusual presentation of malignancy: A case report

Abstract: Renal Clear Cell Carcinoma (RCC) comprises over 80% of renal malignancies in adults. Thyroid gland metastasis is rare in RCC. Few studies have described cases of RCC mistaken for benign arteriovenous malformation (AVM). To the best of our knowledge, an AVM arising from underlying RCC metastasis to the brain has not yet been reported. The current study presents a case of RCC metastasis to the thyroid gland, with an AVM identified to be a result of metastatic involvement in the brain. A 45-year-old African-Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Several reports have recently addressed the relationship of SCN and vascular endothelial growth factor (VEGF) with hypervascularity, which was specifically elevated in both the SCN cyst fluid and lesion tissue [19, 20]. VEGF is crucial for the development of AVM, and previous reports have shown that high VEGF levels in RCC cause acquired AVM [17, 18]. In the present case, microvascular hyperplasia was detected around SCN, and the AVM surrounded the SCN.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Several reports have recently addressed the relationship of SCN and vascular endothelial growth factor (VEGF) with hypervascularity, which was specifically elevated in both the SCN cyst fluid and lesion tissue [19, 20]. VEGF is crucial for the development of AVM, and previous reports have shown that high VEGF levels in RCC cause acquired AVM [17, 18]. In the present case, microvascular hyperplasia was detected around SCN, and the AVM surrounded the SCN.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, acquired-type AVM is generally caused by trauma, tumor, or inflammation [12]. Regarding acquired AVM caused by a tumor, several reports have described cases of acquired AVM due to renal cell carcinoma (RCC), as RCC sometimes induces the development of AVM in the kidney and elsewhere [17, 18]. However, pancreatic AVM around the pancreatic tumor has never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Another report, by Albandar et al. in 2017, described a patient who presented with brain metastasis associated with an AVM 10 …”
Section: Discussionmentioning
confidence: 99%
“…This mutation, when present, may lead to abnormalities of angiogenesis. High levels of hypoxia inducible factor 1α signalling pathway proteins and vascular endothelial growth factor have been found in patients with metastatic disease, and this could possibly explain the development of AVM mimicking tumours during the disease course 10 …”
Section: Discussionmentioning
confidence: 99%
“…AVMs of the thyroid are rare—to date, only five cases have been reported. These lesions are commonly congenital, however, associations with cancer and other states marked by angiogenic stimulation have been highlighted [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%